Immune Cells in the Uterine Remodeling: Are They the Target of Endocrine Disrupting Chemicals? - Meyer, Nicole; Zenclussen, Ana Claudia (Frontiers in Immunology, 2020)
Sufficient uterine remodeling is essential for fetal survival and development. Pathologies related to poor remodeling have a negative impact on maternal and fetal health even years after birth. Research of the last decades yielded excellent studies demonstrating the key role of immune cells in the remodeling processes. This review summarizes the current knowledge about the relevance of immune cells for uterine remodeling during pregnancy and further discusses immunomodulatory effects of man-made endocrine disrupting chemicals on immune cells.